The impact of social amelioration program on Pamantasan ng Lungsod ng Maynila Student-Beneficiaries' Budget Management - Aliazar, Eleonor Victoria E., Cebreros, Hazel B., Cloma, Carisa D., Delarmente, Nicole Anne S., Dig, Mary Christine Erica J., Jordan, Rina Francis B., Lapuz, Steffani Gwen D., Laxamana, Ria Micaella G., Lim, Angela Bianca D., Ranan, Diana Lynn D., Ventura, John Paul G. 4 0 16; 5
ABSTRACT: The study aims to determine the budget management of each PLM student- beneficiary in terms of Fixed Expenses, Flexible Expenses, and Savings as they utilize the allowance from the Social Amelioration Program. It focuses on how PLM student-beneficiaries make use of the monthly allowance. Studying the impact of the Social Amelioration Program (SAP) on college students' budget management would provide information on the decision making that beneficiaries go through after receiving the financial aid as they use it on their Fixed Expenses, Flexible Expenses, and even Savings. The study used a descriptive research design and a quantitative meth od of data collection. The researchers determined that the Social Amelioration Program has a significant effect on the Budget Management of PLM student-beneficiaries in terms of Fixed Expenses, Flexible Expenses, and Savings. The study found that the SAP Allowance uplifts most of the students' academic performance. Additionally, the Social Amelioration Program helps them to be financially equipped which allows the PLM student-beneficiaries to meet and fulfill their educational needs as a college student The importance and benefits of the Social Amelioration Program to students were also seen as it lessens the burden that they are dealing with as they continue studying in the Pamantasan ng Lungsod ng Maynila. The said educational subsidy helps them to accomplish their degrees and graduate eventually for their prosperity. Key words: Social Amelioration Program (SAP), Pamantasan ng Lungsod ng Maynila (PLM) student-beneficiary Budget Management Fixed Expenses, Flexible Expenses, Savings
Business Research: (BSBA major Business Economics) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2